The impact of soccer match play on the muscle damage response in youth female athletes - Hughes, J. D.; Denton, K.; Lloyd, R. S.; Oliver, J. L.; De Ste Croix, M. (International Journal of Sports Medicine, 2018)
Post-match assessment of creatine kinase (CK) activity and delayed-onset muscle soreness (DOMS) are common markers of exercise-induced muscle damage and recovery status in soccer players. These responses have not been examined in youth female players. This study examined the effect of competitive match play on CK activity and DOMS in elite youth players. Thirty-four elite female players, divided into three chronological age groups (U13, n=11; U15, n=10; U17 n=12). Players completed baseline testing for CK and DOMS that was repeated immediately (for DOMS), 80, 128 and 168 h post-competitive match play for CK. Significant time effects were reported for CK (P=0.006) and DOMS (P<0.01). Significant differences between baseline and 168?h post-match were reported for CK (P<0.01), with significant group differences between the U13 and U17 groups for CK (P<0.01). All parameters returned to baseline in U17s at 168 h, but increased CK was evident for U13s and U15s at 168 h. In conclusion, seven days may be insufficient for biochemical recovery in youth female athletes. Therefore, monitoring strategies to assess muscle damage between training and match play should be considered to track recovery and potentially reduce muscular injury risk.